Leukoplakia: An Invasive Cancer Hidden within the Vocal Folds. A Multivariate Analysis of Risk Factors - Klimza, Hanna; Pietruszewska, Wioletta; Rosiak, Oskar; Morawska, Joanna; Nogal, Piotr; Wierzbicka, Małgorzata (Frontiers in Oncology, 2021)
The main problem with the detection of vocal fold leukoplakia (VFL) is knowing exactly what is hidden in the white plaque. The goal of our study was to establish clear diagnostic procedures (diagnostic tools and risk factors) to not miss this cancer under plaque in the presented group of patients with vocal fold leukoplakia. The researchers enrolled 259 patients of which 296 presented vocal fold leukoplakia. All patients were assessed for three classifications, in detail according to NI 2019 and ELS 2015 for blue light and according to Chen 2020 for white light. In 41 of the 296 patients (13.6%), the VFL specimens in the final histology revealed invasive cancer. We compared the results from the classifications to the final histology results. The results showed that the classifications and evaluations of the involvement of anterior commissure improves the clinical utility of these classifications and showed improved diagnostic performance. The AUC of this model was the highest (0.939) with the highest sensitivity, specificity, PPV and NPV (90.2%, 89%, 56.9%, and 98.3%, respectively). An algorithm combining white and blue light along with the combination of the two classifications improves the specificity and predictive value, especially of anterior commissure involvement.